A Reexamination of Tunneling and Business Groups: New Data and New Methods - Siegel, Jordan; Choudhury, Prithwiraj (Review of Financial Studies, 2012)
One of the most rigorous methodologies in the corporate governance literature uses firms' reactions to industry shocks to characterize the quality of governance. This methodology can produce the wrong answer unless one considers the ways firms compete. Because macro-level shocks reverberate differently at the firm level depending on whether a firm has a cost structure that requires significant adjustment, the quality of governance can only be elucidated accurately analyzing a firm's business strategy and their corporate governance. These differences can help one determine whether the fruits of a positive macro-level shock have been expropriated by insiders. Using the example of Indian firms, we show that an influential finding is reversed when these differences are considered. We further argue that the conventional wisdom about tunneling and business groups will need to be reformulated in light of the data, methodology, and findings presented here.